Land use change from permanent rice to alternating rice-shrimp or permanent shrimp in the coastal Mekong Delta, Vietnam: Changes in the nutrient status and binding forms - Kruse, Jens; Koch, Maximilian; Khoi, Chau Minh; Braun, Gianna; Sebesvari, Zita; Amelung, Wulf (The Science of the total environment, 2020)
[Display omitted] •Shrimp introduction improved nutrient status but lead to salt accumulations.•Nutrients accumulated primarily in stable bonding forms.•Shrimp effects were more pronounced in the sludges than in the soils underneath.•Alternating rice-shrimp is a reversible, no-regret soil management strategy.•Permanent shrimp systems adoption option in areas permanently affected by salinity. Saline water intrusion has become a severe threat in the coastal areas of Mekong delta of Vietnam, though offering farmers the option to diversify their land use, and switching, for instance, from permanent rice to alternating rice-shrimp systems or even to permanent shrimp systems. The objective of this study was to evaluate the respective impacts on soil salinity, nutrient status and their binding forms. Hence, we sampled the topsoils (cultivation layer, 0–15 cm) from 10 permanent rice systems and the rice platforms of 10 alternating riceshrimp systems. Furthermore, the sludges and the soils 10 cm underneath of the sludges from the ditches of the alternating rice-shrimp as well as from ponds of the permanent shrimp systems were sampled in Bến Tre and Sóc Trăng provinces, Vietnam, respectively. The samples were analyzed regarding their electric conductivity, total and plant-available nutrient contents. To reveal possible changes in nutrient binding forms, sequential P and S extraction, 31P-nuclear magnetic resonance spectroscopy, and S and P X-ray absorption near edge structure spectroscopy were applied. The results showed that permanent and alternating shrimp cultivation lead to elevated salt concentrations but also improved the overall nutrient status relative to the permanent rice management and especially in the sludges relative to the soils underneath. The continued deposition of shrimp and feed debris promoted the accrual of stable, Ca- and Mg-associated P forms as well as of P-monoesters, whereas the S forms were depleted in thiophene S groups but enriched in sulfides relative to permanent rice fields. As effects by alternating rice-shrimp management were intermediate, this management has more potential to serve as a no-regret strategy for farmers to remain flexible in their response to climate changes and concurrent salinity intrusion relative to permanent shrimp production, which requires strict maintenance of adequate salinity levels also during the rainy season.